2015
DOI: 10.1016/j.molonc.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SOX2 expression induces cell motility via vimentin up‐regulation and is an unfavorable risk factor for survival of head and neck squamous cell carcinoma

Abstract: Recurrent gain on chromosome 3q26 encompassing the gene locus for the transcription factor SOX2 is a frequent event in human squamous cell carcinoma, including head and neck squamous cell carcinoma (HNSCC). Numerous studies demonstrated that SOX2 expression and function is related to distinct aspects of tumor cell pathophysiology. However, the underlying molecular mechanisms are not well understood, and the correlation between SOX2 expression and clinical outcome revealed conflicting data. Transcriptional prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 62 publications
(73 reference statements)
8
68
1
4
Order By: Relevance
“…The present study therefore demonstrated that POSTN expression was elevated in the ESCC tissues with poor differentiation, lymphatic metastasis, venous invasion and thus a severe TNM stage. In terms of the mechanism, POSTN was previously reported to be able to combine to multiple integrin receptors including αvβ3, αvβ5, and α6β4, partially regulating the intracellular signaling pathways linked to phosphatidylinositol 3 kinase (PI3K) /AKT as well as FAK, and sequentially induce the proliferation, metastasis and invasion of cancer cells, and alter tumor microenvironment (11,16,28). The results of the present study validate the negative influences on the ESCC tissue due to the increased POSTN expression in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study therefore demonstrated that POSTN expression was elevated in the ESCC tissues with poor differentiation, lymphatic metastasis, venous invasion and thus a severe TNM stage. In terms of the mechanism, POSTN was previously reported to be able to combine to multiple integrin receptors including αvβ3, αvβ5, and α6β4, partially regulating the intracellular signaling pathways linked to phosphatidylinositol 3 kinase (PI3K) /AKT as well as FAK, and sequentially induce the proliferation, metastasis and invasion of cancer cells, and alter tumor microenvironment (11,16,28). The results of the present study validate the negative influences on the ESCC tissue due to the increased POSTN expression in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…EMT may be directly or indirectly mediated by various factors including snail, slug and twist. Signaling of transforming growth factor-β is considered to exert a pivotal function in triggering and promoting EMT (11 initiation of EMT triggered by twist in prostate cancer (11). As such, POSTN is considered as a key proteins involved in EMT.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the expression and function of key regulators of stemness is context-dependent and might be different in tumor cells as compared to embryonic or adult stem cells. As an example, transcriptional profiling after silencing of Sox2 expression in a HNSCC cell line with amplification of the 3q26 locus (encompassing the Sox2 coding region) revealed a set of upregulated genes related to cell motility and a mesenchymal-like phenotype [56]. Accordingly, silencing of Sox2 accelerated tumor cell migration and invasion, and low Sox2 expression served as a prognosticator to identify HNSCC patients at high risk of treatment failure [56].…”
Section: The Concept Of Cancer Stem-like Cellsmentioning
confidence: 99%
“…Aynı şekilde osteosarkomda Sox2 bir sağkalım faktörüdür ve kendini yenilemede yeni bir biyobelirteç olabileceği önerilmektedir (49). Öte yandan, insan baş-boyun kanser örneklerinde azalmış Sox2 ifadesi vimentin proteinini upregüle ederek, tümör hücre göçünü arttırmıştır (50). Baş-boyun kanserleriyle ilgili meta-analiz sonuçları göstermiştir ki, Sox2 ifadesi, tümör TNM evreleme, invazyon derinliği ve lenf nodül metastazı gibi klinik parametrelerle ilişkilidir (51).…”
Section: Sox2'nin Tümör Başlamasında Ve Gelişiminde Rolüunclassified